THE CONCEPT OF IMAGINARY HOME IN JHUMPA LAHIRI`S “MRS. SEN`S” - Olha V. Yalovenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки, 2019)
Jhumpa Lahiri is a prominent figure in the Asian-American tradition. The complex semantics of heroes` images, the interweaving of plot lines, intertextual connections, the simplicity of presentation, and the dynamic plot development are characteristic features of her writings. The immigrant problems are major in Lahiri`s literary. Most of her characters who are representatives of two cultures find themselves “nowhere”. The article deals with the relationship between cultural and personal identity. The concept of imaginary home as an important factor for the preservation of cultural traditions which is especially relevant in the context of modern transculture, is explored. It is important that immigrants of different generations define the “home” concept in their own way. So, for the first generation, the home is associated with the actual place of birth and identical to nostalgia, past, a sense of cultural loss. As a polysemantic notion, “home” allows a symbolic “journey with the walls”. It means that the character continues to be at home mentally, even though he has left it physically. The main character is a representative of the old diaspora. She continues to be tied with her “home”: living in America, she tries to recreate the artificial life she used to in Calcutta, as well as regaining her “lost identity”. Mrs. Sen lives by the memories and “hides” behind the past, so as not to notice the chaos, the sense of loneliness and inconvenience in her still-artificial American house. The character is “locked” inside, she is deeply lonely, and seems to be distant not only from others, but from herself as well. It is indicated that it is impossible to deny own ethnic origin completely, and that the mixing of two cultures leads to the existence of a character with a hybrid consciousness that does not refuse his roots. Mrs. Sen realizes that only at home in India she feels safe. “Everything is there” means that everything which is valuable to her is left in India. Only details from the past are important for the character: a paper letter from India (not an e-mail), a whole fish with its head which is so hard to find in America and a vibrant sarees collection that no one needs here. Ms. Sen understands that it is just a copy, because she lacks real communication. Symbolically, she imitates “her” and does not want to accept American life which is identified with aggression. The theme of communication (the story shows friendship between two people of different age and origin) is no less important. The characters are very similar because of the loneliness: both Mrs. Sen and Elliot lack complete communication with their relatives. Result in, Mrs. Sen often mentions her home in India because past experience and cultural memory are still important. The character feels lonely in the American society and at the same time, she contrastes herself to others (Mrs. Sen continue to live Indian life), and believes she will never be able to adapt to America completely.